Space oddities : the mysterious anomalies challenging our understanding of the universe - Cliff, Harry (Harry Victor) (Doubleday, 2024)
"An eye-opening account of the inexplicable phenomena that science has only recently glimpsed, and that could transform our understanding of the fundamental nature of reality"--